Selling spirituality : the silent takeover of religion - Carrette, Jeremy R.; King, Richard, 1966- (London ; New York : Routledge, 2005)
Selling Spirituality shows how spirituality today functions as a powerful commodity in the global marketplace, promising to soothe away the ills of modern life whilst functioning as a silent form of economic, cultural and political restraint.
Acknowledgements -- Introduction : spirituality and the rebranding of religion -- 1. A brief history of spirituality -- 2. Western psychology and the politics of spirituality -- 3. Spirituality and the privatisation of Asian wisdom traditions -- 4. Selling the soul : the business of spirituality -- Conclusion : spirituality and resistance : challenging the corporate takeover -- References -- Index.
Includes bibliographical references (pages 183-188) and index.
Print version record.
Added to collection customer.56279.3
Keywords: Spiritual life; Vie spirituelle; RELIGION -- Christianity -- General; RELIGION -- Devotional; BODY, MIND & SPIRIT -- Spirituality -- General; BODY, MIND & SPIRIT -- Inspiration & Personal Growth; RELIGION -- Spirituality; Spiritual life; Spiritualiteit; Internationalisatie; Geistliches Leben; Religionsphilosophie; Electronic books